Enactment of IDEF0 models for the purpose of systems simulation - Lieu, Ann Horng. (2008)
This dissertation describes an approach to the enactment of IDEFO models for the purpose of systems simulation. The approach involves: 1) the enhancement of an IDEFO model to include additional information about system behavior and IT infrastructure. 2) The establishment of a standard format for storing model data in neutral files, easily accessible and interpreted by various simulators. 3) The development of a simulator having the capability to read and interpret a set of neutral data files (GSD standard) and simulate the model. 4) The integration of curve fitting software to analyze the output data from simulation and to complete the feedback loop to IDEFO model for approximate modeling.